THE INFLUENCE OF SUPERVISION PERFORMANCE AND SCHOOL PRINCIPAL MANAGERIAL COMPETENCY ON SCHOOL PRINCIPAL PERFORMANCE - Slamet Riyadi; Tuti Puspitasari; Susatyo Adhi Pramono; Tjutjun Setiawan; Regina Yoantika Natalie (Jurnal Scientia, 2023)
The purpose of this study is to quantify and examine how school supervisors' managerial oversight and managerial expertise affect school principals' performance. This study employs descriptive-inferential methodology and quantitative research techniques. Observation, interviews, and documentation studies were used to obtain data. Statistical tests are then used to process and interpret the data. The entire research sample consisted of school administrators. The whole population census approach was employed in the sampling technique. According to the analysis of research findings, supervisory managerial oversight had a strong, immediate impact on the school's managerial competency. The effectiveness of school A principals is not significantly impacted by management oversight of supervisors. The performance of school A principals is significantly impacted directly by the managerial ability of school principals. Through the managerial proficiency of school principals, supervisory management supervision has a strong indirect impact on the performance of school A principals. The management oversight of school supervisors does not differ significantly from other managerial oversight. The managerial capabilities of school principals vary significantly. The principals of school A are more managerially skilled than the principals of school B. There is a large disparity between school principal performance; principals at school A perform better than principals at school B.